A graphical method for comparing nocturnal oxygen saturation profiles in individuals and populations: Application to healthy infants and preterm neonates. Issue 5 (24th March 2018) - Terrill, Philip I.; Dakin, Carolyn; Edwards, Bradley A.; Wilson, Stephen J.; MacLean, Joanna E.
Abstract: Study Objectives: Pulse‐oximetry (SpO2 ) allows the identification of important clinical physiology. However, summary statistics such as mean values and desaturation incidence do not capture the complexity of the information contained within continuous recordings. The aim of this study was to develop an objective method to quantify important SpO2 characteristics; and assess its utility in healthy infant and preterm neonate cohorts. Methods: An algorithm was developed to calculate the desaturation incidence, depth, and duration. These variables are presented using three plots: SpO2 cumulative‐frequency relationship; desaturation‐depth versus incidence; desaturation‐duration versus incidence. This method was applied to two populations who underwent nocturnal pulse‐oximetry: (1) thirty‐four healthy term infants studied at 2‐weeks, 3, 6, 12, and 24‐months of age and (2) thirty‐seven neonates born <26 weeks and studied at discharge from NICU (37‐44 weeks post‐conceptual age). Results: The maturation in healthy infants was characterized by reduced desaturation index (27.2/h vs 3.3/h at 2‐weeks and 24‐months, P  < 0.01), and increased percentage of desaturation events ≥6‐s in duration (27.8% vs 43.2% at 2‐weeks and 3‐months, P  < 0.01). Compared with term‐infants, preterm infants had a greater desaturation incidence (54.8/h vs 27.2/h, P  < 0.01), and these desaturations were deeper (52.9% vs 37.6% were ≥6% below baseline, P  < 0.01). The incidence of longer desaturations (≥14‐s) in preterm infants was correlated with healthcare utilization over the first 24‐months ( r  = 0.63, P  < 0.01). Conclusions: This tool allows the objective comparison of extended oximetry recordings between groups and for individuals; and serves as a basis for the development of reference ranges for populations.